The Students’ Performance in Homeroom Guidance as Predictor of the Academic Achievement of Grade 10 Students in Makabayan Subjects at Bendita National High School Magallanes District, Division of Cavite - U. Tirona, Neill (ASEAN Journal of Education, 2023)
This study investigated the effects of students’ performance in Homeroom Guidance (HG) on the academic achievement of grade 10 students in Makabayan subjects. The researcher used descriptive-correlational method of research. Wherein, it focused on describing the relationship of the dependent and independent variables. Moreover, the data were collected from 102 students enrolled in Bendita National High School, District of Magallanes during the academic year 2020-2021. The students rating from Homeroom Guidance (HG) subject and their scholastic records in Araling Panlipunan (AP), Edukasyon sa Pagpapahalaga (ESP), Technology and Livelihood Education (TLE) and Music, Arts, Physical Education & Health (MAPEH) were analyzed. Accordingly, the result of the HG assessment showed that students were still in the “Developing” level. In terms of the academic achievement in Makabayan subjects, the students were “Satisfactory” with an overall mean of 83.05. Furthermore, based on the results of the regression analysis, HG performance significantly affects the academic achievement of the students in AP (R=.467a, F=27.816, p=.000, p<.05); ESP (R=.631a, F=66.092, p=.000, p<.05); MAPEH (R=.553a F=43.970; p=.000, p<.05) and TLE (R=.513a F=35.788, p=.000, p<.05). Additionally, all of the learning areas have shown positive relationship as shown in the R-value. This study is limited to the grade 10 level population whereas the researcher intends to extend the study to other grade level and eventually, will be utilized in policy creation and other related programs. With the aforementioned, conclusions were drawn and recommendations were offered.